Sexual and gender-based violence victims' satisfaction of the support services through the holistic model of care in the Democratic Republic of Congo - Gilbert M. Mugisho; Raha Maroyi; Solange Nabami; Amani C. Kasherwa; Ali Bitenga; Denis Mukwege (Springer, 2022)
Abstract Background The quality-of-care assessment is an important indicator of the efficiency of a healthcare system. In the Democratic Republic of the Congo (DRC), despite the implementation of the holistic care model for the treatment of sexual and gender-based violence (SGBV) victims, little is known about the client's perception of this model and its outcome. This study aimed to examine the expected and perceived satisfaction of service recipients through the One-Stop-Center model of health care in eastern DRC. Methodology This descriptive and analytical cross-sectional study was conducted at Panzi Hospital (PH), in eastern DRC. Data were collected by a mixed-methods approach, 64 Victims of Sexual Violence participated in individual (in-depth) interviews and 150 completed the Survey. The Kruskal-Wallis test was used to compare the mean item scores of sexual violence victims' satisfaction. Results The findings from our qualitative analysis demonstrated that the victims admitted at PH had various expectations and needs on arrival depending on their social identity and residence locations. For instance, the VSVs coming from remote areas with ongoing armed conflicts mentioned concerns related to their security in the post-treatment period and the risks of re-victimization that this could incur. Conversely, those who came from the urban neighborhood, with relative security raised various concerns related to their legal reparation and ongoing access to other support services. With scores above 4, victims of sexual violence were extremely satisfied with the overall care provided and wished that PH could continue to support them mentally and financially for an effective reintegration into their communities. The Kruskal-Wallis analysis confirmed statistically significant differences (p < 0.1) in satisfaction with legal support based on the victims' residential locations, social support based on their age groups, occupational therapy based on their religious denominations, and accommodation based on their professional activity. Conclusions Results of this study suggest that victims' satisfaction with support services is based on either the organizational frameworks of clinical or support services within the hospital and the victims' social environment.